Protein Insufficiency Among First-Trimester Pregnant Women in Jambi, Indonesia - Herlambang, Herlambang; Puspasari, Anggelia; Maharani, Citra; Enis, Rina Nofri; Fitri, Amelia Dwi; Kusdiyah, Erny; Ibnu, Ismi Nurwaqiah (Althea Medical Journal, 2025)
Background: Insufficient protein intake or specific patterns of plasma amino acid levels during pregnancy has been associated with adverse maternal and neonatal outcomes. Studies in non-pregnant women have reported an association between protein intake and amino acid levels, however, data in pregnant women remain limited. Jambi, a region rich in freshwater fish, has a traditional dishes based on fish, which may affect maternal protein adequacy. This study aimed to assess protein sufficiency intake, plasma essential amino acid levels, and the relationship between fish consumption and protein intake among first-trimester pregnant women. Methods: A cross-sectional study was conducted in 2022 involving pregnant women at 9-16 weeks of gestation in Jambi, Indonesia, selected through purposive sampling. Protein intake and fish consumption data were collected using Food Frequency Questionnaires. Plasma essential amino acid levels were measured using Liquid Chromatography-Mass Spectrometry. Bivariate analyses were performed using Mann-Whitney and Chi-square tests.Results: Among 30 participants, 23.3% had insufficient protein intake and had lower plasma essential amino acid levels. Lysine levels showed a statistically significant difference between groups (p=0.010). Women with adequate protein intake reported significant higher fish consumption, particularly of freshwater fish (p=0.033).Conclusion: Adequate protein intake during early pregnancy is related to higher plasma essential amino acid levels. Consumption of local freshwater fish contributes to maintaining sufficient protein intake. These findings emphasize the importance of integrating healthy dietary patterns and locally sourced nutrient-rich foods into prenatal care to support maternal wellness and long-term health outcomes.